(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Surgical site infection (SSI) is a major postoperative complication following abdominal surgery and contributes significantly to postoperative morbidity, prolonged hospital stay, and increased healthcare costs. Emergency laparotomy procedures are associated with a higher risk of SSI due to contamination from gastrointestinal contents and compromised physiological status of patients.¹² Methods: A prospective randomized comparative study was conducted in a tertiary care teaching hospital over six months. Seventy-four patients undergoing emergency laparotomy were randomized into two groups. Group A (n=37) received a subcutaneous negative pressure drain prior to wound closure, whereas Group B (n=37) underwent wound closure without drain placement. Patients were monitored for surgical site infection, wound complications, and duration of hospital stay. Results: Surgical site infection occurred in 5.4% of patients in the drain group compared with 27% in the non-drain group (p=0.024). Wound inflammation was more common in the control group (32.4%) compared with the drain group (10.8%). The mean hospital stay was significantly shorter in the drain group (3.92 days) compared with the control group (5.49 days) (p<0.01). Conclusion: Subcutaneous negative pressure drainage significantly reduces surgical site infection and postoperative hospital stay following emergency laparotomy.